EFFECTIVITY BETWEEN LEMONGRASS STEW AND CINNAMON INFUSION IN REDUCING BLOOD GLUCOSE LEVEL IN DIABETES MELLITUS PATIENTS - Susanti, Susanti; Bistara, Difran Nobel (Lux Mensana: Journal of Scientific Health, 2023)
Introduction: Diabetes mellitus is a chronic metabolic disorder brought on by insufficient insulin production by the pancreas or inefficient insulin utilization by the organism. This study determines the effectivity between cinnamon infusion and lemongrass stew in reducing blood glucose levels in diabetes mellitus patients. Method: This study uses a design pra-experimental by method two-group pre-post design. The sample of this study were diabetics who were willing to be respondents as many as 20 people. The dependent variable is blood glucose levels, the independent variables are lemongrass stew and cinnamon infusion. The instrument used is the observation sheet. Result & Analysis: test results for lemongrass stew with cinnamon infusion were obtained in treatment group 1 (p = 0.502) and treatment group 2 (p = 0.730) where α > 0.05, meaning that statistically there was no difference in blood glucose levels reduction between treatment groups 1 (lemongrass) and treatment group 2 (cinnamon). Discussion: There was no difference in reducing blood glucose levels between treatment group 1 (lemongrass) and treatment group 2 (cinnamon).